Peningkatan Kemampuan Mengidentifikasi Unsur Intrinsik Teks Drama Melalui Model Pembelajaran The Power Of Two SMP Negeri 3 Sitolu Ori - Viktor Risman Zega (Universitas Nias, 2022)
This study aims to determine whether the power of two learning model is effectively used in identifying the intrinsic elements of drama texts, while the specific goal is to increase students' ability to identify the intrinsic elements of drama texts through the power of two learning model. The subjects of this study were students of class VIII-1 SMP Negeri 3 Sitolu Ori totaling 35 people consisting of 18 males and 17 females. This research uses Classroom Action Research (CAR). The results of this study obtained the average value of students from 66.07 in the first cycle and became 85.23 in the second cycle. Increased student activity also experienced an increase with the results in the first cycle of the first meeting 40.00%, and the second meeting 57.14%. In the second cycle the first meeting with the results of 85.71%, and the second meeting 91.43%. Based on the results of research conducted by researchers proved that the power of two learning models can improve students' ability to identify the intrinsic elements of drama texts and an increase in student activity